A kin-selection model of fairness in heterogeneous populations. (21st May 2023) - Wild, Geoff; Flear, Vonica J.; Thompson, Graham J.
Abstract: Humans and other primates exhibit pro-social preferences for fairness. These preferences are thought to be reinforced by strong reciprocity, a policy that rewards fair actors and punishes unfair ones. Theories of fairness based on strong reciprocity have been criticized for overlooking the importance of individual differences in socially heterogeneous populations. Here, we explore the evolution of fairness in a heterogeneous population. We analyse the Ultimatum Game in cases where players' roles in the game are determined by their status. Importantly, our model allows for non-random pairing of players, and so we also explore the role played by kin selection in shaping fairness. Our kin-selection model shows that, when individuals condition their behaviour on their role in the game, fairness can be understood as either altruistic or spiteful. Altruistic fairness directs resources from less valuable members of a genetic lineage to more valuable members of the same lineage, whereas spiteful fairness keeps resources away from the competitors of the actor's high-value relatives. When individuals express fairness unconditionally it can be understood as altruistic or selfish. When it is altruistic, unconditional fairness again serves to direct resources to high-value members of genetic lineages. When it is selfish, unconditional fairness simply improves an individual's own standing. Overall, we expand kin-selection based explanations for fairness to include motivations other than spite. We show, therefore, that one need not invoke strong reciprocity to explain the advantage of fairness in heterogeneous populations. Highlights: Primates are thought to enforce fairness by engaging in strong reciprocity. Strong reciprocity overlooks kin selection and social heterogeneity, say critics. We show how heterogeneity leads to fairness via kin selection. Fairness diverts resources toward an individual's high-status relatives. Fairness keeps resources away from the competitors of high-status relatives.